2000
DOI: 10.1243/0957650001538263
|View full text |Cite
|
Sign up to set email alerts
|

Emissions characteristics of higher alcohol/gasoline blends

Abstract: An experimental investigation was conducted to determine the emissions characteristics of higher alcohols and gasoline (UTG96) blends. While lower alcohols (methanol and ethanol) have been used in blends with gasoline, very little work has been done or reported on higher alcohols (propanol, butanol and pentanol). Comparisons of emissions and fuel characteristics between higher alcohol/gasoline blends and neat gasoline were made to determine the advantages and disadvantages of blending higher alcohols with gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(53 citation statements)
references
References 15 publications
1
50
0
1
Order By: Relevance
“…Combustion studies with ethanol in SI engines have been carried out by [2][3][4][5][6][7], focusing on performance characteristics, while others [8][9][10][11] have concentrated on engine emission measurements; most of these were done on Port Fuel Injection (PFI) engines. Very few studies have been conducted in latest technology Direct Injection Spark-Ignition (DISI) engines that are typically very sensitive to fuel properties; more to the point, in some of those studies, certain trends illustrate great diversity.…”
Section: Combustion Of Alcohol Blends In Enginesmentioning
confidence: 99%
“…Combustion studies with ethanol in SI engines have been carried out by [2][3][4][5][6][7], focusing on performance characteristics, while others [8][9][10][11] have concentrated on engine emission measurements; most of these were done on Port Fuel Injection (PFI) engines. Very few studies have been conducted in latest technology Direct Injection Spark-Ignition (DISI) engines that are typically very sensitive to fuel properties; more to the point, in some of those studies, certain trends illustrate great diversity.…”
Section: Combustion Of Alcohol Blends In Enginesmentioning
confidence: 99%
“…Alcohols, considered a renewable resource, are being extensively investigated in all fields. Unlike traditional fuels, alcohols contain oxygen, which is beneficial for complete combustion and the reduction of toxic emissions [1][2][3][4][5][6][7][8]. Specifically, light alcohols, e.g., methanol and ethanol, have been successfully utilized as octane boosters for traditional fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Engine tests suggest that oxygen content in the alcohol fuel is relevant to the knocking resistance and the harmful emissions of NO x , soot and carbonyl [2,3,32]. Gautam et al [2,3] investigated the combustion and emission characteristics of a single-cylinder engine fueled with C1-C5 alcohol-gasoline blends. It was concluded that with the increase of oxygen content in the fuel blends, knocking resistance is enhanced, but NO x emissions are increased significantly at high compression ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Chao et al (2000) indicated that using ethanol gasoline blended fuels increases the emission of formaldehyde, acetaldehyde and acetone several times than those from gasoline. Gautam et al (2000) investigated the emissions characteristics between higher alcohol/gasoline blends and neat gasoline. It was found that the cycle emissions of CO, CO 2 and organic matter hydrocarbon equivalent from the higher alcohol/gasoline blends were very similar to those from neat gasoline.…”
Section: Introductionmentioning
confidence: 99%